Some biological properties of leptospira manilae - Famatiga, Estela Guinto
The presence of some biological characteristics of presently known pathogenic leptospira in L. manilae are presented. The Bile-salt-alcohol extract of L. manilae renders human ?O? erythrocytes agglutinable by anti-L. Manilae serum; the culture and culture supernate cause lysis of sheep?s red blood cells; and pathological lesions are produced on CAM of chick embryo. In vitro, the organism is very sensitive to tetracycline.